Inventarisasi Jenis Kupu-kupu pada Hutan Kerangas di Kawasan Cagar Alam Mandor Kabupaten Landak - Ari Hepi Yanti, Margareta Florida, Tri Rima Setyawati, (Jurnal Protobiont, 2015)
The butterfly is one of the fauna found in the area of Mandor Nature Reserve needs to bepreserved and have a benefit asenvironmental health bioindikator. This research aims to know the type and the level of diversity of butterflies on heath lands at Mandor Nature Reserve. Research methods used are field observation with outbound techniques in three different habitats, namely in the area of forest, forest edge and open areas. The research results obtained 15 types of butterflies that is Acraea violae, Appias libythea, Catopsilia pyranthe, Euploea mulciber, Eurema sari, Hypolimnas bolina, Junonia orithya, J. atlites, Letopsia nina, Neptis hylas, Papilio demodocus, P. helenus, P. polytes, P. memnon, and Parantica agleoides. Index of Diversity (H') of butterfly was founded ranged between 1.1602 - 2.1661 with average of diversity 1.7051. Index of equity (E) ranged between 0.4184 – 0.7813 with average 0.6104 that’s shows level of high equity. Index of Dominance (D) ranged between 0.1328-0.4297 with the average 0.2509 that shows there is no type of butterflies that dominates on site research.